2022
DOI: 10.1155/2022/5171525
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Activity of Ferula assafoetida Oleo-Gum-Resin (Asafoetida) against TNF-α-Stimulated Human Umbilical Vein Endothelial Cells (HUVECs)

Abstract: Inflammation is the body’s biological reaction to endogenous and exogenous stimuli. Recent studies have demonstrated several anti-inflammatory properties of Ferula species. In this paper, we decided to study the anti-inflammatory effect of ethanolic extract of Ferula assafoetida oleo-gum-resin (asafoetida) against TNF-α-stimulated human umbilical vein endothelial cells (HUVECs). HUVECs were cultured in a flat-bottom plate and then treated with ethanolic extract of asafoetida (EEA, 0-500 μg/ml) and TNF-α (0-100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The primary human endothelial cells obtained from the umbilical vein (HUVEC) were extensively investigated as a human model of endothelial cells to assess the effects of senolytic and senomorphic compounds [ 26 , 27 , 28 , 29 ]. We observed that 10 µg/mL of ZOE exerts anti-inflammatory activity on LPS-stimulated yHUVEC by reducing the expression levels of IL-1β, IL-8, MCP-1, TNF-α, and ICAM-1.…”
Section: Discussionmentioning
confidence: 99%
“…The primary human endothelial cells obtained from the umbilical vein (HUVEC) were extensively investigated as a human model of endothelial cells to assess the effects of senolytic and senomorphic compounds [ 26 , 27 , 28 , 29 ]. We observed that 10 µg/mL of ZOE exerts anti-inflammatory activity on LPS-stimulated yHUVEC by reducing the expression levels of IL-1β, IL-8, MCP-1, TNF-α, and ICAM-1.…”
Section: Discussionmentioning
confidence: 99%
“…The posttreatment mRNA levels of ICAM-1 and VCAM-1 were measured by reverse transcription-PCR (RT-PCR) using previously described primers for real-time PCR analysis. The relative mRNA expression was presented as normalised VCAM-1 and ICAM-1 mRNA to glyceraldehyde 3-phosphate dehydrogenase (GAPDH) mRNA by the 2 –ΔΔCT method ( 10 , 30 ). The levels of the ICAM-1 and VCAM-1 proteins in HUVECs were determined by Western blotting.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, the Kazakhs have used F. soongarica to treat headaches, colds and stomach aches, F. caspica can treat nervous breakdown, and F. lehmannii is used as an anti-parasitic, for anti-malnutrition and to cure cold and pain in the heart and abdomen [ 12 , 15 ]. A number of modern pharmacological and biological studies have indicated that Ferula has anticancer [ 19 , 20 ], anticarcinogenic [ 21 ], antimicrobial [ 22 ], antidiabetic [ 23 ], anti-flu [ 24 ], anti-inflammatory [ 25 , 26 ], and cardiovascular system effects [ 27 ], as well as use against Alzheimer’s disease [ 28 , 29 ] and in anti-neuropathic pain [ 30 ] activities.…”
Section: Introductionmentioning
confidence: 99%